South-habitat. a journey through autogenerated settlements of the andean territory (2007)
This article presents the summary of the document written to achieve an Architect degree at the National University of Colombia in 2006, thesis tutored by the geographer Anne Catherine Chardon: [HABITATSUR] SOUTHHABITAT. A Journey through Autogenerated Settlements of the Andean Territory. The work presents the results of a research that studies four cases; four cities constructed beyond official planning, located in the Andean cities of La Paz (Bolivia), Cuzco (Peru), Quito (Ecuador) and Manizales (Colombia). This research is conceived under the perspective of the habitat as a central concept, thus, a dissertation on this concept is made among the implications and the employment of it in planning and construction of cities. From the theorization on the term is set a reflection on the inequality and the segregation that Latin American and Andean cities impose to its inhabitants. Finally, auto-generated settlement is proposed as a concept to study these phenomena from its own formal, social and historical characteristics. Under this perspective, the research proposes a methodology that establishes two moments of analysis: the formation and the transformation of the settlement. At every moment two processes are analyzed: the appropriation, focused in the construction of the house and the relations of the home with the neighborhood; and the “territorialización”, focused in the physical-space and social organization of the neighborhood, and in its relations with the city and the State. These processes are analyzed under variables of legality, space type, sociality and aesthetics, soon to make a comparative study between the studied cities, differentiating between the capital and intermediate cities. Finally there is a dissertation on the ways that from architecture and the academy, could be proposed and improved the Latin American urban habitat.